Kesehatan Bank Perkreditan Rakyat Dalam Perhitungan Camel (Pada PT. BPR Anugerahdharma Yuwana Jember) - Suryadinata, Ningrum; Anisa Putri, Nava Rindi (Majalah Ilmiah DIAN ILMU, 2023)
Analysis to maintain the health of a rural bank is not only assessed onthe development of financial factors, but the level of asset health, management,income, and the ability to pay debts and receivables. The purpose of this study isto measure and determine the health condition of BPR ADY Jember financialperformance in 2019-2021. The method used in this study is descriptivequantitative using CAMEL analysis (capital, asset quality, management,earning, and liquidity) by assessing banking financial statements. This type ofresearch uses descriptive quantitative research using secondary data onfinancial statements of PT. BPR ADY Jember in 2019 — 2021. The data analysistechnique used is a descriptive analysis technique, namely by calculating andanalyzing the minimum, maximum, average ratio with the CAMEL method forcalculation and as an object of research. The result of this study is thedevelopment of the health level of financial performance in the healthy categoryin capital, assets, and management, but of the five CAMEL criteria that areclassified as healthy, the level of earning health is directly proportional to thehealthy category with liquidity. When the ROA value that shows the bank'sability to earn profits decreases, the level of the bank's ability to pay CRobligations also decreases. Although capital, assets, and management areclassified as healthy, they are unable to support the bank's ability to pay itsshort-term obligations (Cash Ratio).